A virtual electrical drive control laboratory - Gokbulut, Muammer; Bal, Cafer; Dandil, Besir (Wiley, 2006)
Neural and fuzzy courses are widely offered at graduate and undergraduate level due to the successful applications of neural and fuzzy control to nonlinear and unmodeled dynamic systems, including electrical drives, However, teaching students a neurofuzzy controlled electrical drive in a laboratory environment is often difficult for schools with limited access to expensive equipment facilities. Therefore, computer simulations and dedicated software are needed to assist the students in visualizing the concepts and to provide graphical feedback during the learning process. In this article, an educational software is proposed for the neuro-fuzzy control of induction machine drives. The tool helps students learn the application of neuro-fuzzy control of electrical drives. The software has a flexible structure and graphical user interface. The neuro-fuzzy architecture, the motor and load parameters can be easily changed in the developed software. Neuro-fuzzy control performance of induction motors can be monitored graphically for various control structures and current controllers. (C) 2006 Wiley Periodicals, Inc.
Keywords: neuro-fuzzy control; induction motors; educational software